CCAFS and partners' three investment outcome pathways are associated with more than USD 3.5 billion Climate Smart Agriculture investments globally - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The work of CCAFS and partners over the last 10 years in the research and engagement arenas has influenced the investment decisions of a diverse range of investors globally. This has been achieved via multiple investment-oriented outcome pathways and entry points for influencing public and private sector actors in a wide range of countries. The lessons that are being distilled from these experiences will continue to guide future investment planning for resilient and climate-smart food systems.